2021
DOI: 10.1001/jamapediatrics.2021.2482
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Depressive and Anxiety Symptoms in Children and Adolescents During COVID-19

Abstract: IMPORTANCE Emerging research suggests that the global prevalence of child and adolescent mental illness has increased considerably during COVID-19. However, substantial variability in prevalence rates have been reported across the literature.OBJECTIVE To ascertain more precise estimates of the global prevalence of child and adolescent clinically elevated depression and anxiety symptoms during COVID-19; to compare these rates with prepandemic estimates; and to examine whether demographic (eg, age, sex), geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

108
1,148
16
39

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,551 publications
(1,546 citation statements)
references
References 72 publications
(130 reference statements)
108
1,148
16
39
Order By: Relevance
“…could also have led to the higher rates of mental health problems found in the present study. However, our results are roughly in line with systematic reviews of cross-sectional studies on the impact of the pandemic [ 2 , 3 ]. Those reviews have reported an increase of mental health problems, with only very few studies reporting no negative mental health impact during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…could also have led to the higher rates of mental health problems found in the present study. However, our results are roughly in line with systematic reviews of cross-sectional studies on the impact of the pandemic [ 2 , 3 ]. Those reviews have reported an increase of mental health problems, with only very few studies reporting no negative mental health impact during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…There is increasing empirical evidence of psychological distress among children and adolescents during the pandemic according to systematic reviews of mostly cross-sectional studies [ 2 , 3 ]. These reviews describe an average doubling of clinically elevated anxiety (21%) and depression (25%) symptoms [ 2 ] and high pooled prevalences of depression (29%), anxiety (26%), sleep disorders (44%), and posttraumatic stress symptoms (48%), respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the impact on the mental health of children and adolescents has increased, including anxiety, depression and disturbances in sleep and appetite [ 30 ]. In a global meta-analysis, the prevalence estimates of children and adolescent depression and anxiety were 25.2% and 20.5% during COVID-19, respectively [ 31 ]. Compared with pre-pandemic estimates, the prevalence of depression and anxiety symptoms during COVID-19 have doubled.…”
Section: Epidemiological Burden Of Covid-19 In Childrenmentioning
confidence: 99%
“…About COVID-19 and the psychological well-being of children and adolescents, data show that mental disorders in children and adolescents increased significantly in the first year of the pandemic, by 25.2% and 20.5%, respectively. Anxiety, depression, uncertainty and loneliness doubled during the pandemic with a prevalence in older adolescents and girls [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%